A quasi-dimensional SI burn rate model for carbon-neutral fuels - Hann, Sebastian (Springer Vieweg, 2021)
Sebastian Hann describes the development of a quasi-dimensional burn rate model that enables the prediction of a fuel variation, without the need for a recalibration of the model. The model is valid for spark-ignition combustion engines powered by conventional and carbon-neutral fuels. Its high predictive ability was achieved by modeling the fuel-dependent laminar flame speed based on reaction kinetics calculations. In addition, the author discards a fuel influence on flame wrinkling by performing an engine measurement data analysis. He investigates the fuel influence on engine knock and models it via ignition delay times obtained from reaction kinetics calculations. Contents Fuel Influence on Flame Wrinkling Laminar Flame Speed Model Burn Rate Model Improvement Engine Knock Investigation and Modeling Target Groups Scientists and students in the field of automotive engineering, esp. thermodynamics and 0D/1D engine simulation Calculation and development engineers in industry working in the field of thermodynamics, esp. combustion engine development About the Author Sebastian Hann works as a research assistant in the field of 0D/1D simulation at the Institute of Automotive Engineering, University of Stuttgart. He dealt with the investigation and modeling of the fuel influence on spark-ignition engine combustion and engine knock. In addition to conventional fuels, he also considered carbon-neutral fuels.